2022
DOI: 10.1108/ijwbr-07-2021-0040
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the wellness dimensions of wine tourism experiences: a netnographic approach

Abstract: Purpose In a post-COVID world, tourists seeking wellness through unique tourism experiences is expected to intensify. The purpose of this study is twofold – to provide baseline information to explore interlinkages between wine tourism and wellness and to identify wine tourism experiences that create a sense of wellness among wine tourists. Design/methodology/approach This study adopts a netnographic approach by analysing user-generated content collected from the TripAdvisor platform. A total of 2,117 reviews… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 76 publications
0
10
0
Order By: Relevance
“…The hedonic experience associated with F&B is reflected in the pleasure derived from what one eats and drinks; in this sense, several authors have identified how tourists' visits to specific wellness and spa resort and destinations are characterized by this type of experience (Laki cevi c et al, 2021;Kiatkawsin and Han, 2017). In this logic, alcohol consumption is also depicted as a hedonic, short-lived and relaxing experience (Kim and Yang, 2021), which is why wine consumption can also positively impact the well-being of tourists (Kotur, 2022;Fiore et al, 2019).…”
Section: Fandb In the Wellness Experiencementioning
confidence: 99%
See 1 more Smart Citation
“…The hedonic experience associated with F&B is reflected in the pleasure derived from what one eats and drinks; in this sense, several authors have identified how tourists' visits to specific wellness and spa resort and destinations are characterized by this type of experience (Laki cevi c et al, 2021;Kiatkawsin and Han, 2017). In this logic, alcohol consumption is also depicted as a hedonic, short-lived and relaxing experience (Kim and Yang, 2021), which is why wine consumption can also positively impact the well-being of tourists (Kotur, 2022;Fiore et al, 2019).…”
Section: Fandb In the Wellness Experiencementioning
confidence: 99%
“…, 2021; Kiatkawsin and Han, 2017). In this logic, alcohol consumption is also depicted as a hedonic, short-lived and relaxing experience (Kim and Yang, 2021), which is why wine consumption can also positively impact the well-being of tourists (Kotur, 2022; Fiore et al. , 2019).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Studies have highlighted the importance of authenticity in enhancing wine tourism experiences by way of tourists engaging in extraordinary activities, savouring local food and wines unique to the place (Ali-Knight and Carlsen, 2003; Cambourne and Macionis, 2000; Quadri-Felitti and Fiore, 2012). Kotur (2022) explored the interlinkages between wine tourism experiences and individual’s holistic wellness using Dunn’s wellness model (1959). Cohen and Ben-Nun (2009) highlighted that consumer experiences played a vital role in strengthening the bond between wine tourists and wine brands.…”
Section: Introductionmentioning
confidence: 99%
“…The concept of “wellness” is holistic; many scholars emphasize the multidimensional nature of personal health, combining physical and mental health, social, and environmental factors. It is explained as a state where one experiences “harmony in mental, physical, spiritual, or biological health in general” through healthy and enriching activities ( Kotur, 2022 ). Wellness has five main conceptualizations: wellness as a state of being or outcome, as a process, as an approach to professional care, as a matter of community, and as a global topic ( Stará and Peterson, 2017 ).…”
Section: Introductionmentioning
confidence: 99%